ANALISIS KEMAMPUAN PERAWAT DALAM PENCEGAHAN INFEKSI NOSOKOMIAL DI LANTAI 6B MENGGUNAKAN METODE NVIVO DI RSU ROYAL PRIMA BULAN JAN - JUNI TH 2022 - Deborah Angelin Purba; Sri Wahyuni Nasution; Chrismis Novalinda Ginting (Jurnal Penelitian Pendidikan IPA, 2023)
Nosocomial infection is an infection originating from a hospital caused by hospital staff or health workers during the health service process or hospital visitors. The background of this research is the lack of role of nurses in the process of preventing nosocomial infections. The purpose of this study was to explain the role of nurses in preventing nosocomial infections at RSU Royal Prima. This type of research uses a qualitative approach method with in-depth interviews with informants in order to know clearly and in depth the role of nurses in preventing nosocomial infections at RSU Royal Prima. The results showed that nurses already know their role in terms of reporting to the doctor if there are signs and symptoms of infection and implementing isolation of infectious diseases and maintaining prevention while on duty at the hospital. However, there are still nurses who do not know their role optimally in terms of maintaining hospital cleanliness. In maintaining hand hygiene, nurses only know their role in terms of washing hands, the implementation is not in accordance with procedures. In using Personal Protective Equipment, nurses know their role in terms of wearing masks and gloves, but in practice there are still nurses who have not used Personal Protective Equipment according to standards. In addition, there are obstacles for nurses in preventing nosocomial infections such as inadequate infrastructure